A educadora Maria Laura: contribuições para a constituição da educação matemática no Brasil - Pereira, Pedro Carlos (2010)
Taking the oral history as a guiding point, and desiring to contribute in the clarification of the history of Mathematics Education in Brazil, this work is based on contributions developed by Professor Maria Laura Mouzinho Leite Lopes to increasingly solidify the Brazilian Mathematics education. The guideline of the work is developped from the analytical look of her career, of national and international academic trajectory. During this journey, there is a moment in which Professor Maria Laura takes knowledge of how to teach and learn Mathematics under the French methodology presented by IREM. The nuclear theme of this research is to show how the life and work of Prof. Maria Laura is intrinsic to the moment when Maths education begins to be established in Brazil and how she influenced this moment. Another point raised are the interventions given by Prof. Maria Laura in the establishment of scientific societies in the area of Mathematics and Mathematics Education in Brazil, research groups and post-graduate courses in Maths Education in Rio de Janeiro, as well as a legacy consisting of books released by different publishers, papers published in various magazines, training courses for teachers and mathematics educators and the participation in congresses